Paramedic analgesia comparing ketamine and morphine in trauma (PACKMaN): a randomised, double-blind, phase 3 trialResearch in context - Michael A. Smyth; Hannah Noordali; Kath Starr; Joyce Yeung; Ranjit Lall; Felix Michelet; Gordon Fuller; Stavros Petrou; Alison Walker; Zoe Green; Rebecca McLaren; Elisha Miller; et al. (The Lancet Regional Health. Europe)
Summary: Background: Paramedics frequently administer analgesic medications for pain following trauma. Morphine is the most commonly administered strong analgesic. However, it may not be the best option as it may lower blood pressure, depress respiration and there is a risk of dependency. Ketamine might be a better option due to speed of onset and favourable side-effect profile. We sought to compare clinical effectiveness of paramedic administered ketamine and morphine in patients with severe pain following trauma. Methods: PACKMaN was a double-blinded, randomised controlled, superiority trial, conducted in two regional ambulance services in the UK. Eligible patients were 16 years of age or over, had an acute injury, and articulated a pain score of 7 or greater on a 0–10 numeric rating score (NRS). We excluded pregnant patients, prisoners, those unable to articulate a pain score and anyone lacking capacity. The randomisation list prepared by the study programmer, utilised a permuted, unstratified, block randomisation system (variable size blocks) to achieve an overall ratio of 1:1 control (morphine): intervention (ketamine). Treatment packs were identical in appearance, apart from their unique sequential number. Individual participant randomisation occurred when the attending paramedic opened the treatment pack. The maximum available dose of morphine was 20 mg while the maximum available dose of ketamine was 30 mg. The treating paramedic administered the trial drug slowly, in regular small aliquots, via the intravenous (or intraosseous) route, titrating treatment until the patient reported adequate analgesia or requested that treatment stop due to undesired side effects. Timing of drug administration was not prespecified. The primary outcome was the Sum of Pain Intensity Difference (SPID) score on arrival to the hospital, calculated using patient reported NRS scores. Analysis was performed on an intention to treat basis. PACKMaN is registered with the International Clinical Trials Registry (ISRCTN14124474). Findings: PACKMaN recruited its first patient on 10/11/2021 and achieved its recruitment target on 16/05/2023. We randomised 449 participants: 219 (49%) received ketamine and 230 (51%) received morphine. The SPID score was 3.5 (SD 2.8) for ketamine and 3.4 (SD 3.0) for morphine. We found no significant difference in efficacy between drugs (adjusted mean difference 0.1, 95%CI −0.4 to 0.6, p = 0.74). There was no significant difference in the incidence of serious adverse events [4 (2%) ketamine; 8 (3%) morphine]. There were no treatment related deaths. Interpretation: Ketamine did not provide superior analgesia than morphine when used by paramedics to treat acute severe trauma pain. Unexpected adverse events occurred infrequently. Despite analgesia, many patients still experienced pain on arrival at hospital, highlighting the need for further research. Funding: PACKMaN was funded by the National Institute for Health and Care Research.